Research on the therapeutic effectiveness of the veterinary medicinal product “Surfadev” in complex therapy for stimulating sexual desire in cows - O. A. Katsaraba; R. M. Sachuk; Ye. Ye. Kostyshyn; Y. S. Stravskyy; L.-M. Ye. Kostyshyn (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Clinical studies were conducted in the treatment of hypofunction of the ovaries to increase the fertility of cows and heifers with the newly created drug “Surfadev” (solution for injections) in complex therapy. VLZ “Surfadev” (solution for injections). The drug stimulates the secretion of gonadotropins by the pituitary gland in a maximum of 2–3 hours after administration. The increased content of gonadotropins in the blood persists for 4–5 hours after administration. Unlike natural luliberin, the biological activity of the drug is 50 times greater, which allows the use of this drug in microdoses and short courses. The drug decomposes under the influence of enzymes more slowly than natural luliberin, which provides a stronger biological effect on the pituitary gland. “Devivit Complex” is a complex multivitamin preparation (Vitamins A, D3, E, B1, B2, B3, B5, B6, B12), which is used to correct and normalize metabolic processes in animals. Vitamins included in the preparation take part in biochemical processes in animal organisms (in the form of enzyme vitamins, hormone vitamins, antioxidants). When ovarian function is stimulated or corrected, 90.0 % of the treated animals show the arousal stage of the sexual cycle within 3–15 days, and their fertilization rate from the first insemination is 70.0 % on average. The high efficiency of using “Surfadev” in combination with “Devivit Complex” for ovarian hypofunction has been established. 83.3–95.6 % of the treated cows showed sexual desire, and the fertility from the first insemination reached 70.0 %. Further studies will be the next stage of pre-registration trials aimed at studying the effectiveness of the veterinary drug “Surfadev” (solution for injections) in complex therapy in the treatment of ovarian hypofunction and follicular cysts, which is mandatory material of the fourth part “Preclinical and clinical documentation” of the dossier for this medicine.